Establishment of a novel double‐monoclonal antibody sandwich enzyme‐linked immunosorbent assay (ELISA): tool for human B7‐H4 detection in autoimmune diseases. (6th June 2021) - Ding, Sisi; Zhou, Hengxin; Gu, Yanzheng; Shen, Yu; Zhang, Li; Zhao, Huayang; Wu, Jian; Zhang, Xueguang; Chang, Xin; Liu, Cuiping
Summary: B7‐H4, one of the immunoregulatory proteins, plays an inhibitory role by inhibiting T cell proliferation and cytokine production. Nevertheless, the significance of soluble B7‐H4 (sB7‐H4) in autoimmune diseases is unclear. In our study, we developed two novel mouse anti‐human B7‐H4 monoclonal antibodies (mAbs) (clones 8D4 and 7E1) with utilities for flow cytometry, immunoblotting and immunofluorescence. We characterized 7E1 as a functional antibody with antagonistic activity, which could promote T cell proliferation and regulate cytokine production. Furthermore, based on the different epitope specificities, we established a novel enzyme‐linked immunosorbent assay (ELISA) which could detect sB7‐H4 sensitively and specifically. Using this ELISA kit, sB7‐H4 was observed in a high proportion of autoimmune diseases patients. We found that the levels of sB7‐H4 were significantly higher in patients with systemic lupus erythematosus (SLE), type I diabetes (T1D) and Graves' disease (GD). Together, sB7‐H4 in human serum is regarded not only as a regulator of T cell activation but may also be a diagnostic marker of autoimmune diseases. Abstract : Based on two novel monoclonal antibodies with different epitope specificities, we successfully established an enzyme‐linked immunosorbent assay (ELISA) system, which can detect human soluble B7‐H4 (sB7‐H4) sensitively and specifically. The ELISA kit provides a valuable tool to measure the levels of sB7‐H4 in autoimmune diseases.